Pharmacist Malpractice Over the Last Decade in the United States - Rhee, Diane; Nalliah, Romesh Priyanthan (Journal of Pharmacy Practice and Community Medicine)
Background: The National Practitioner Databank is a database that lists all malpractice cases against healthcare professionals. There is no study considering the trends in pharmacy malpractice using official data from the National Practitioner Databank in recent times. Methods: In the current study, we used the National Practitioner Databank for period 2006-2015 to evaluate trends numbers of malpractice payments and adverse actions enforced against pharmacists in the United States. JMP was utilized to visualize and evaluate data. Results: During the decade of the study there were 646 malpractice payments made against pharmacists and 2015 represents the fifth consecutive year of increase in the annual number of malpractice payments against pharmacists. Contrastingly, numbers of adverse actions against pharmacists has experienced the fifth consecutive year of reduction. Hence, malpractice payments are trending upward while adverse actions against pharmacists are trending downward. Conclusion: Although the pharmacy profession implements multiple processes to protect patients from medication errors the number of malpractice payments against them continues to rise.
Keywords: Malpractice; Malpractice Payments; Licensure; Adverse Action; Healthcare Delivery